Towards a Single and Comprehensive Notion of 'Civilian Population' in Crimes against Humanity - Alija Fernández, Rosa Ana (International criminal law review, 2017)
Although an essential element of the definition of crimes against humanity is that a civilian population be targeted, there is no agreement on what 'civilian population' means in this context. The notion has been given different meanings depending on whether the crimes are committed in times of conflict or peacetime. In times of conflict, preference is given to a broad approach based on international humanitarian law. More problematic is the attribution of a specific content to the notion in peacetime, where even discrimination has been suggested as a defining criterion. In this article we contend that a single notion of civilian population in crimes against humanity applicable in every circumstance is needed. Hence, we suggest determining the civilian population on the basis of the rules on State responsibility in international human rights law and general international law in order to exclude those endowed with public authority from the civilian population